IMPROVING THE UNDERSTANDING OF THE COMMUNITY ABOUT THE CONCEPT OF COMMUNITY-BASED TOURISM - Latupapua, Yosevita Th; Soselisa, Fanny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The availability of potential natural tourist attractions in a place must also be supported by the readiness of human resources through increasing community understanding and skills. The purpose of doing service is to improve the understanding and skills of the community in preparing quality natural tourist attraction objects, and to train how to assess the potential of tourism objects based on weighting and scoring according to ADO guidelines. The method used is socialization, observation, and evaluation. The results of the service showed that there was an increase in knowledge and interest in learning from all participants who attended, this was evidenced by the post test results which showed that there was an increase in the value of understanding the concept of tourist attraction objects, community-based tourism concepts, forms of quality participation and the ability to assess objects based on scoring. This socialization activity is also able to motivate the people of Abubu to develop the potential of existing objects with the readiness of facilities for visitors, as well as foster self-confidence to later be involved in managing natural and cultural resources as quality tourism products.